Sıcaklık Terselmesi ve Hava Kirliliği (SO) İlişkisi: Manisa Örneği. - Olcay, Hilal; Çukur, Hasan (Electronic Turkish Studies)
Due to Manisa’s large fertile agricultural lands, freshwater resources, and various underground resources, as well as its proximity to Izmir and ease of transportation, industrial activities are intensively carried out. Urbanization, population, and energy use are also increasing rapidly due to industrial activities. As a result of the growth of settlements and industrial areas towards the plain floor, air pollution problems are frequently encountered, especially in the winter season. In addition to these human resources, climate and topographical features also play a significant role in air pollution. As a result of the fact that the eastern and northeastern sides of Manisa are open, but the western side is topographically closed by a threshold, the polluted air is trapped over the city by the northeasterly winds. Due to the lack of suitable corridors to carry the polluted air out of the city, the air quality in the Menemen Strait to the west is deteriorating. In this study, it is aimed to determine the temperature inversion that occurs because of the interaction of climatic conditions and topography and the effects of inversion on air quality. In this direction, meteorology (temperature, pressure, and wind) records and air quality sulfur dioxide (SO) data of the Manisa meteorological station covering the period 2006-2023 were utilized. As a result of the study, it was determined that the pressure values and the number of frosty days increased during the periods when the amount of pollution (SO) in the field increased, while the temperature and wind speed increased during the periods when the amount of SO decreased. The prevailing wind direction can be taken into consideration in the positioning of new industrial facilities and settlements to be established in Manisa, and geothermal energy can be used for their heating.